(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: Every year, millions of preventable deaths and disabilities were directly and indirectly caused by smoking. Various methods have been employed and millions of dollars have been spent in order to tackle this issue. Objectives: This study was designed to identify the factors associated with knowledge, attitude and quitting attempts to smoking among adult population in Sarawak. Materials and Methods: This was a cross-sectional study conducted among the adult population in Sarawak. Data were collected from ten villages in Kota Samarahan and Kuching Division by face to face interview using modified Global Adult Tobacco Survey (GATS) questionnaire. Non-probability sampling method was adopted to select the villages. All the households of the villages were visited, and an adult member was selected randomly from each house irrespective of the sex. After missing value imputation, a total of 1000 data were analysed using statistical software SPSS 19.0 version. Results: Analysis showed that 28.8% of the respondents were current smokers. Multiple Linear Regression Analysis (MLR) revealed that younger age, family size, marital status, scariness and in formativeness of Pictorial Health Warnings (PHWs) significantly contributed to perceived knowledge of health effects of smoking (p<0.05). Similarly level of education, perceived knowledge of health effects and information on cigarette packages have significant positive contribution to preventive attitude towards smoking, whereas non smoking status has no influence on the attitude towards smoking (p<0.05?. On the contrary, marital status, clarity and nature of information on the cigarette packages about PHWs have significantly influence for quitting attempts (p<0.05), whereas the nature of jobs such as business and service had no influence in quitting attempt of smoking (p<0.05). Conclusion: Despite numerous interventions programme for tobacco control being implemented such as PHWs, the study findings revealed that better plans and strategies for more effective preventive measures against smoking should be instituted by policy makers. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.266-273